Controle químico de doenças fúngicas do trigo em diferentes cultivares e locais de cultivo - Baumgratz, Ivete Schwantes (2009)
Wheat is a cereal crop planted from the State of Rio Grande do Sul to the central region of Brazil. Wheat cultivars and cropping conditions vary significantly and influence the occurrence of wheat diseases and their need for control. In susceptible wheat cultivars the chemical control is widely used, but it is not always profitable, which demands previous analyses of its economics. This was the subject of this field research carried out in 2007 in Palmeira das Missões and Passo Fundo counties, located 130 km apart from each other, with the wheat cultivars Coodetec 114, Ônix, Safira, Pampeano, Fundacep 30, and Fundacep Nova Era, chosen because their differences in disease susceptibility. Seeds were treated with the insecticide imidacloprid (Gaucho®, 100 mL.100 kg seeds-1) or imidacloprid plus the fungicide triadimenol (Baytan®, 270 mL). The plants were later sprayed once (at elongation, booting, or flowering), twice (elongation + booting, elongation + flowering, booting + flowering), or three times (elongation + booting + flowering) with the fungicide tebuconazol + trifloxystrobin (Nativo®, 600 mL.ha-1 + adjuvant Lanzar®, at 0.5%). Evaluations included assessments of emerged plants, disease severity, grain yield, and weight of grain hectoliters. After harvest, results were tested for profitability based upon wheat prices and application costs effective in November of 2007. The 2007 average temperatures and rain amount favored the occurrence of leaf rust, leaf spots, and wheat scab in both locations. Seed treatment with triadimenol reduced powdery mildew and leaf rust in early plant stages, but it was not profitable at the end. Better results were obtained with three sprays of fungicide in Passo Fundo or two applications (booting + flowering) in Palmeira das Missões. Chemical control of wheat diseases is very important for better yields, but its profitability vary with plant genotype, locations, and crop management